Variational Problems with Partial Fractional Derivative: Optimal Conditions and Noether's Theorem. (2nd October 2018) - Jiang, Jun; Feng, Yuqiang; Li, Shougui
Abstract : In this paper, the necessary and sufficient conditions of optimality for variational problems with Caputo partial fractional derivative are established. Fractional Euler-Lagrange equations are obtained. The Legendre condition and Noether's theorem are also presented.